2010
DOI: 10.1177/104063871002200204
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Methods for Detecting Anaplasma Marginale Infection in Lactating Dairy Cattle of Puerto Rico

Abstract: Abstract. Bovine anaplasmosis (BA) is a hemoparasitic disease of great importance in cattle within the tropical and subtropical regions of the world. Control programs for BA require accurate diagnostic assays but validation can be challenging because the true disease status of all animals is frequently not known with certainty. The objective of this study was to estimate the accuracy of assays for detection of Anaplasma marginale infection in lactating dairy cattle of Puerto Rico using Bayesian methods without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Area under the estimated ROC curve (AUC) was calculated by the trapezoid approximation method (Munem and Foulis, 1984). More information concerning latent class models based on ordinal classifications can be found elsewhere (Fosgate et al, 2007;Fosgate et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Area under the estimated ROC curve (AUC) was calculated by the trapezoid approximation method (Munem and Foulis, 1984). More information concerning latent class models based on ordinal classifications can be found elsewhere (Fosgate et al, 2007;Fosgate et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The agro-ecological and geoclimatic conditions of India are highly favorable for growth and multiplication of ticks that act as natural vectors of anaplasmosis (Minjauw and Mcleod 2003). Anaplasmosis causes significant magnitude of economic losses due to low weight gain, reduction in milk production, abortion, and cost of treatments (Fosgate et al 2010). A. marginale infects mature erythrocytes by an endocytic process and exit by exocytosis from infected erythrocytes to attack other fresh erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…34 A comparative study reported that PCR has a low sensitivity of 67% due to variable parasitemia levels in chronically infected animals. 10 In addition, PCR methods need significant effort to prevent false-positive results, which affect the diagnostic specificity of the assay. 32 A recombinant major surface protein 5 (rMSP5)-based cELISA has proven useful for serological detection of Anaplasma-infected animals in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Such assays have been used to detect carrier cattle and include complement fixation (CF), 13 card agglutination, 13,21 indirect enzyme-linked immunosorbent assay (ELISA), 8 dot ELISA, 22 competitive ELISA (cELISA), 19 and indirect fluorescent antibody test (IFAT). 13,29 Most of these assays have diagnostic specificities higher than 96% 2,3,10,[22][23][24][25]29 ; however, the diagnostic sensitivities vary greatly. 10,34 Complement fixation test has a very high specificity, but reports of sensitivity range from 20% 4 to 70%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation